Translocation of positively and negatively charged polystyrene nanoparticles in an in vitro placental model. Issue 7 (October 2015) - Kloet, Samantha K.; Walczak, Agata P.; Louisse, Jochem; van den Berg, Hans H.J.; Bouwmeester, Hans; Tromp, Peter; Fokkink, Remco G.; Rietjens, Ivonne M.C.M.
Highlights Polystyrene nanoparticle translocation was studied in a BeWo b30 transwell model. One positively and two negatively charged polystyrene nanoparticles were tested. The results reveal limited translocation of PS-NPs across the BeWo cell layer. Translocation of PS-NPs was not related to charge. The BeWo b30 model can be a screening method to set priorities for further testing.